A review on biomass-fired CHP system using fruit and vegetable waste with regenerative organic Rankine cycle (RORC). (2021) - Kavathia, Karn; Prajapati, Parth
Abstract: As the rising concern of waste management around the world, landfills are stacking up the waste due to a shortage of land. Researchers are finding different ways to convert this waste heat to produce useful energy. Effective treatments of these waste results in the utilization of products generated by the system. Many limitations of the Organic Rankine Cycle (ORC) and anaerobic digestion are yet to be solved. Anaerobic digestion is the biological system which helps in degradation of organic waste into useful products. The product generated is burnt to heat organic working fluid present in Organic Rankine Cycle (ORC) by supplying heated medium through the evaporator. Although pre-treatment is required for food waste. The paper reviews the combined heat and power (CHP) systems between biomass and regenerative Organic Rankine Cycle (ORC), which affects requirement and efficiency of system using dry fluid as the medium of Organic Rankine Cycle (ORC). In this reviewed paper, the steady-state conditions are kept into consideration to observe the factors affecting the efficiency of the system done by various authors to get a better performing system.